Manual descriptivo de puestos del área regional para la empresa Chiquita Brands - Sancho-Artavia, María Laura (Instituto Tecnológico de Costa Rica, 2014)
This project consists on the development of a Manual of Jobs Descriptions for the regional area of the Chiquita Brands Company. This study is divided into two volumes. The first of these consists of five chapters, which are distributed in the following way: - The first chapter covers general aspects of the company as well as the study. It also includes the justification of the study, the problem and the objectives. - The second chapter contains all the theoretical foundations that supported this study. - The third chapter covers the methodology used to carry out this project. - The fourth chapter corresponds to the detailed analysis of the jobs positions, based on the information gathered during the interview with partners. The conclusions and recommendations of this section supports the proposal of this study. - In Chapter five, the conclusions and general recommendations of the study are presented. - Then, the abbreviations and the glossary of the terms used to describe the job positions are presented. - Finally, the references are included. The second volume consists of the proposal of the fifty job descriptions that were subjected to study. This section is distributed in the following manner: - The first chapter contains an overview of the manual and includes specifications, update and instructions for its use. - The second chapter contains the description of the fifty jobs studied, which are sorted according to the administrative unit to which they belong. - Finally the abbreviations and the glossary of terms are presented.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2014.
Keywords: Organización; Administración; Eficiencia; Eficacia; Competencia; Variables